ANALISIS PERUBAHAN SIFAT MEKANIK DAN STRUKTUR MIKRO BESI COR NODULAR 700 SETELAH MENGALAMI PROSES PERLAKUAN PANAS - Rochim Suratman; Beny Bandanadjaja (Mesin, 2002)
Ferro casting ductile 700 (FCD 700) is a ferrous material with carbon content > 2 %. It has pearlitc microstructure with a little amount of ferrite and nodular graphite. In as-cast condition FCD 700 has tensile strength 700 N/mm2 , elongation 2 % min. , hardness 229